Aktivitas Belajar Peserta Didik dengan Pembelajaran Literasi, Orientasi, Colaborasi dan Refleksi (Loc-R) di SMP Negeri 7 Kota Ternate - Hernita Pasongli; Eva Marthinu; Julianto La Taju; Syarifuddin Adjam; Facriah Djumati; M. Ikhsan (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
The lack of use of learning models makes teaching and learning activities less effective and interesting. The lecture learning model commonly used by teachers in teaching and learning activities is often considered boring by students and student learning activities are low. The purpose of this study was to determine the activities of students with the application of the Literacy, Orientation, Collaboration and Reflection Learning Model (LOC-R) at SMP Negeri 7 Ternate City. The research method is descriptive research with a quantitative approach. The research sample was VIIc SMP Negeri 7 Ternate City. The number of samples selected was 35 students consisting of 23 girls and 12 boys. The sample in this study was class VIIc students, the sample was selected by purposive sampling by taking into account the characteristics of students. Collecting data using observation sheets and study documentation. Analysis of the data used is the percentage formula with categorization criteria. The results obtained by student activities at the appreciative stage were 79.9%, literacy stage was 82.8%, orientation stage was 88.4%, collaboration stage was 85.4% and reflection stage was 94.4%. Student learning activities using the LOC-R learning model are very effectively implemented in the classroom